Matching book thickness of generalized Petersen graphs - Zeling Shao; Huiru Geng; Zhiguo Li (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
The matching book embedding of a graph G is to place its vertices on the spine, and arrange its edges on the pages so that the edges in the same page do not intersect each other and the edges induced subgraphs of each page are 1-regular. The matching book thickness of G is the minimum number of pages required for any matching book embedding of G, denoted by mbt(G). In this paper, the matching book thickness of generalized Petersen graphs is determined.